Kandungan Antioksidan Pada Daun Kelor (Moringa Oleifera) dan Potensi Sebagai Penurun Kadar Kolesterol Darah - Angelyn Tjong; Youla A. Assa; Diana S. Purwanto (Universitas Sam Ratulangi, 2021)
Abstract: One of the biggest risk factors for cardiovascular disease is hypercholesterolemia. Cholesterol is an important fat, however if it is excessive in the blood it can cause various diseases, one of which is cardiovascular disease. One of the traditional medicines used to reduce blood cholesterol levels is Moringa Oleifera leaves, which contain flavonoids and play an important role in lowering blood cholesterol levels. This study aimed to determine the antioxidant content of Moringa Oleifera leaves, the benefits of lowering blood cholesterol levels, and the dosage of administration. This study was conducted by using three databases, namely PubMed, ClinicalKey and Google Scholar to find articles which met the inclusion and exclusion criteria, then the assessment was carried out. There was a significant reduction in blood cholesterol levels when given Moringa leaves, as well as the dose given. In conclusion, antioxidants in Moringa leaves can reduce cholesterol levels in the blood.Keywords: antioxidants, moringa leaves, cholesterol, cardiovascularÂ Â Abstrak: Salah satu faktor risiko terbesar penyakit kardiovaskular adalah hiperkolesterolemia. Kolesterol merupakan lemak yang penting, namun jika berlebihan dalam darah dapat menyebabkan berbagai penyakit, salah satunya kardiovaskular. Salah satu obat tradisional yang digunakan untuk menurunkan kadar kolesterol darah adalah daun kelor (Moringa Oleifera), yang mengandung flavonoid dan berperan penting dalam menurunkan kadar kolesterol darah. Tujuan penelitian ini untuk mengetahui kandungan antioksidan daun kelor, manfaat sebagai penurun kadar kolesterol darah, dan dosis pemberian. Pencarian artikel menggunakan tiga database yaitu PubMed, ClinicalKey, dan Google Scholar untuk menemukan artikel sesuai dengan kriteria inklusi dan eksklusi, kemudian dilakukan penilaian. Terdapat penurunan kadar kolesterol darah yang signifikan ketika diberikan daun kelor dalam menurunkan kadar kolesterol darah, serta dosis yang diberikan. Sebagi simpulan, antioksidan pada daun kelor dapat menurunkan kadar kolesterol dalam darah.Â Kata Kunci: antioksidan, daun kelor, kolesterol, kardiovaskular